ChemInform Abstract: Simple and Clean Photoinduced Aromatic Trifluoromethylation Reaction. Issue 44 (13th October 2016) - Li, Lu; Mu, Xiaoyue; Liu, Wenbo; Wang, Yichen; Mi, Zetian; Li, Chao‐Jun
Abstract: A metal‐ and oxidant‐free trifluoromethylation of unactivated arenes and heteroarenes under either ultraviolet or visible light irradiation is presented.